(untitled) (Global Journal of Management and Business Research, 2017)
Microfinance is a source of financial services for entrepreneurs and small businesses lacking access to banking and related services. Micro finance is emerging as a powerful instrument for poverty alleviation in the new economy. Beyond the direct linked with poverty reduction, it is an indirect link to address the issues of health, education and gender. Micro finance cover not only consumption and production loans, but will also include other credit needs such as housing and shelter improvements.